The Stunting Paradox in Yemen: Misaligned Priorities in Humanitarian Crisis Response - Dewi, Nafisa Quraisyita (JURNAL ISLAM NUSANTARA, 2025)
This study aims to analyze the paradox of stunting in Yemen, particularly the disconnect between humanitarian response priorities and children's actual nutritional needs amid the ongoing conflict. Stunting, a form of chronic malnutrition, is a significant public health issue in Yemen, exacerbated by the conflict's disruption of food, healthcare, and sanitation systems. Despite the clear evidence of rising stunting rates, international humanitarian interventions tend to focus on addressing acute crises, such as extreme hunger, while neglecting long-term nutritional needs. Using a qualitative literature review approach, the research synthesizes data from archival documents, reports, and secondary sources to explore the structural causes of stunting and the challenges faced by humanitarian actors in Yemen. The findings reveal that the protracted conflict, economic collapse, and humanitarian blockades have worsened food insecurity and malnutrition. Moreover, the humanitarian response often prioritizes short-term survival over long-term prevention of stunting, resulting in a lack of integrated, multisectoral interventions. The study emphasizes the need for a paradigm shift in humanitarian policies to incorporate long-term development strategies and integrate stunting prevention. This research contributes to the academic understanding of the humanitarian-development nexus and offers recommendations for more holistic interventions.